Perceptions of In-Charge Teachers of Mid-Day Meal Scheme in India: Case Study of UT Chandigarh - Prakasam, Seepana (INDIAN EDUCATIONAL REVIEW, 2016)
This paper is based on a field study conducted on 50 Mid-Day Meal Scheme in-charge teachers in 50 government schools across the Union Territory of Chandigarh. The objectives of the study were to understand the consumption pattern of the cooked Mid-Day Meal by the school going children under Mid-Day Meal Scheme. The majority of the respondent teachers felt that the quality of mid-day meal is average, and it has positive impact in terms of increase in enrolment and attendance but indifferent about increase in attention towards studies. Some of the children do not take food due to reasons like lack of parent’s permission, food not tasty, repetition of the same food, distribution of food much earlier than lunch time. There was no unanimity among the teachers, whether the implementation of Mid-Day Meal was satisfactory or not by the Chandigarh administration. The in-charge teachers stated that Chandigarh administration spends reasonably large amount of money as subsidy, but it is not sufficient if quality of food and service delivery is not improved. Involvement of parents is necessary in setting up menu. There is a need to reduce infrastructural bottlenecks and, instead of distribution of food from the centralised kitchens, it is better to decentralise kitchens for better supervision. There is also a need to enhance nutritional standards of the meal.